Cameroon : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2010)
The Cameroonian authorities found irregularities while implementing the first Poverty Reduction Strategy Paper (PRSP). The process of revising the strategy of PRSP I has resulted in the growth and employment strategy paper (GESP), designed for achieving the MDGs and realizing the vision with multiyear development programs. The GESP deals with a review of development policies, its vision and goals, a growth and employment strategy, state governance and strategic management, macroeconomic and budgetary guidelines, and an institutional framework. The GESP programming and monitoring system thus will help in formulating better policies.